Implementasi Hukum Hak Ingkar Notaris Terhadap Kerahasiaan Isi Akta Notaris - Erwina Junita Sari (Faculty of Law Universitas Islam Indonesia, 2022)
The present study identifies the legal implementation of the notary's right to deny the confidentiality of the contents of the notarial deed based on Notary Position Law (Undang-Undang Jabatan Notaris, UUJN) and the Notary's Code of Ethics. The problems formulated are: first, does the notary have the right of refusal? Second, how is the right of Notary Denial in the perspective of UUJN and the Notary’s Code of Ethics? Third, how is the implementation of the Notary's right of refusal to the contents of the Notary's deed? This is a normative research which is additionally supported by data from informants and employs the statutory and conceptual approaches. Legal materials were analyzed descriptively qualitatively. The results of this study concluded that first, the Notary has the right of refusal (i.e. not to speak or provide information before investigators, the Notary Supervisory Board, the Notary Honorary Council and before the Panel of Judges) as long as the right of refusal is related to the Notary's work. Second, from the UUJN perspective of the notary's right to disavow, it is mandatory to apply in order of maintaining the confidentiality of the contents of the deed made based on Articles 4 and 16 of the UUJN and from the Perspective of the Notary’s Code of Ethics, Notaries must uphold the UUJN and maintain the dignity of their position of trust by which not to reveal the confidentiality of the contents of the deed they made. Third, the implementation of the Notary's right of refusal in keeping the contents of the deed confidential cannot be carried out properly because there are still many Notaries who do not carry out their obligations not to provide information about the deed they made because they are afraid to face the summons process when asked for information by investigators or Judges.Key Word: Notary’s Refusal Right, Content of the Notary Deed, UUJN and Notary’s Code of Ethics AbstrakPenelitian ini menulis tentang implementasi hukum hak ingkar notaris terhadap kerahasiaan isi akta notaris berdasarkan UUJN dan Kode Etik Notaris. Masalah yang dirumuskan adalah, pertama: apakah Notaris mempunyai hak ingkar? Kedua, bagaimana hak Ingkar Notaris dalam perspektif UUJN dan Kode Etik Notaris? Ketiga, bagaimana implementasi hak ingkar Notaris terhadap isi akta Notaris? Jenis penelitian ini adalah Normatif yang didukung dari keterangan narasumber dengan pendekatan perundang-undangan dan pendekatan konseptual. Bahan hukum dianalisis secara deskriptif kualitatif. Hasil penelitian tersebut menyimpulkan bahwa pertama, Notaris mempunyai hak ingkar untuk tidak berbicara atau memberikan keterangan dihadapan penyidik, Majelis Pengawas Notaris, Majelis Kehormatan Notaris dan didepan Majelis Hakim sepanjang hak ingkar tersebut merupakan berhubungan dengan pekerjaan Notaris. Kedua, perspektif UUJN hak ingkar Notaris wajib untuk digunakan dalam menjaga rahasia atas isi akta yang dibuat berdasarkan Pasal 4 dan 16 UUJN dan Perspektif Kode Etik Notaris, Notaris menjunjung tinggi UUJN serta menjaga harkat dan martabat jabatan kepercayaan untuk tidak membuka rahasia atas isi akta yang dibuatnya. Ketiga, pelaksanaan hak ingkar Notaris dalam menjaga rahasia isi akta yang dibuatnya belum bisa dijalankan sebagaimana mestinya karena masih banyak Notaris yang tidak menjalankan kewajibannya untuk tidak memberikan keterangan mengenai akta yang dibuatnya karena takut untuk menghadapi proses pemanggilan ketika diminta keterangan oleh penyidik atau Hakim.Kata-kata Kunci: Hak Ingkar Notaris, Isi Akta Notaris, UUJN dan Kode Etik Notaris